Blocking CTLA-4 while priming with a whole cell vaccine reshapes the oligoclonal T cell infiltrate and eradicates tumors in an orthotopic glioma model. (2nd January 2018) - Field, Cameron S.; Hunn, Martin K.; Ferguson, Peter M.; Ruedl, Christiane; Ancelet, Lindsay R.; Hermans, Ian F.
ABSTRACT: Vaccine-mediated cancer treatment is unlikely to induce long-term survival unless suppressive mechanisms are overcome. Given the success of antibody-mediated immune checkpoint blockade in relieving regulation of endogenous anti-tumor T cell responses in tumor-burdened hosts, we investigated whether checkpoint blockade could improve the efficacy of responses induced with a whole tumor-cell vaccine. We show that administration of a single dose of blocking antibody was sufficient to significantly enhance antitumor activity of the vaccine, inducing complete radiological regression of established intracranial tumors. The antibody or vaccine alone were ineffective in this setting. The antibody had to be administered before, or close to, vaccine administration, suggesting CTLA-4 blockade had an impact on early priming events. The combined treatment resulted in enhanced trapping of leukocytes in the lymphoid tissues, including T cells that had undergone significant proliferation. There were no obvious changes in the stimulatory function of antigen-presenting cells or the number and function of regulatory T cells, suggesting T cells were the targets of the checkpoint blockade. While tumors regressing under combined treatment were highly infiltrated with a variety of leukocytes, tumor eradication was dependent on CD4 + T cells. Analysis of the TCR repertoire showed that the addition of anti-CTLA-4 at priming reshaped the repertoire of tumor infiltrating T cells. In particular, the oligoclonal populations became greater in magnitude and more diverse in specificity. Using anti-CTLA-4 in a restricted way to promote the priming phase of an anti-cancer vaccine may offer a useful way of harnessing clinical benefit from this powerful agent.